The Role of Human Dendritic Cells in HIV-1 Infection - Ahmed, Zahra; Kawamura, Tatsuyoshi; Shimada, Shinji; Piguet, Vincent (Journal of investigative dermatology, 2015)
Dendritic cells (DCs) and their subsets have multifaceted roles in the early stages of HIV-1 transmission and infection. DC studies have led to remarkable discoveries, including identification of restriction factors, cellular structures promoting viral transmission including the infectious synapse or the interplay of the C-type lectins, Langerin on Langerhans cells (LCs), and dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin on other DC subsets, limiting or facilitating HIV transmission to CD4+ T cells, respectively. LCs/DCs are also exposed to encountering HIV-1 and other sexually transmitted infections (herpes simplex virus-2, bacteria, fungi), which reprogram HIV-1 interaction with these cells. This review will summarize advances in the role of DCs during HIV-1 infection and discuss their potential involvement in the development of preventive strategies against HIV-1 and other sexually transmitted infections.